2018
DOI: 10.3390/catal8100413
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ce Doping of a Co/Al2O3 Catalyst on Hydrogen Production via Propane Steam Reforming

Abstract: We synthesized cerium-doped cobalt-alumina (CoxCey/Al2O3) catalysts for the propane steam reforming (PSR) reaction. Adding cerium introduces oxygen vacancies, and the oxygen transfer capacity of the Ce promoter favors CO to CO2 conversion during PSR, inhibiting coke deposition and promoting hydrogen production. The best PSR activity was achieved at 700 °C using the Co0.85Ce0.15/Al2O3 catalyst, which showed 100% propane (C3H8) conversion and about 75% H2 selectivity, and 6% CO, 5% CO2, and 4% CH4 were obtained.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The addition of a small amount of rare earth oxides in the catalyst as a promoter has received considerable attention from different researchers [13,14]. CeO 2 , as an effective redoxagent, can convert between Ce 4+ and Ce 3+ to achieve the conversion between oxygen and oxygen vacancies, resulting in a good oxygen storage capacity [15]. Thus, this work explores the effect of dispersion, particle size, and the reduction ability of the active component of Ni with the addition of CeO 2 based on Ni-Cu/HZSM-5 (Ni:Cu = 8:1).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of a small amount of rare earth oxides in the catalyst as a promoter has received considerable attention from different researchers [13,14]. CeO 2 , as an effective redoxagent, can convert between Ce 4+ and Ce 3+ to achieve the conversion between oxygen and oxygen vacancies, resulting in a good oxygen storage capacity [15]. Thus, this work explores the effect of dispersion, particle size, and the reduction ability of the active component of Ni with the addition of CeO 2 based on Ni-Cu/HZSM-5 (Ni:Cu = 8:1).…”
Section: Introductionmentioning
confidence: 99%
“…The XRD patterns of the Co-containing samples is comparable to those of the Co-free samples (Fig. 3), with an absence of clear peaks characteristic of either Co 3 O 4 or metallic Co. 62 This can be attributed to the low Co-content used in these samples or to a high dispersion of small Co particles that cannot be detected by XRD.…”
Section: Resultsmentioning
confidence: 67%
“…61 Cerium introduces oxygen vacancies that can lead to higher conversion of CO to CO 2 during propane steam reforming, for example, preventing carbon deposition and resulting in higher hydrogen production. 62 It has been reported that oxygen defects on the surface of the catalyst play an important role in enhancing CO 2 adsorption, activation, and conversion by hydrogenation into methane. 63 Liu et al 64 revealed an improvement in CO 2 conversion from 45 to 71% upon the addition of 2 wt% CeO 2 to Ni/Al 2 O 3 catalyst during CO 2 methanation at 300 °C and 15 000 ml h −1 g −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the lack of a reliable distribution network and a safety management handling requires H 2 to be produced from suitable feedstock. The latter can comprise either water electrolysis or hydrocarbons steam reforming [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies exist in literature and each one delves into a specific area of analysis. Experimental studies that deal with C1-C2 [10][11][12], C3-C4 [9,13], and higher hydrocarbons [14][15][16][17] have already postulated that modeling studies are necessary in order to properly comprehend the system dynamics that involve the interaction of several subsystems. As these subsystems operate continuously and sequentially, such modeling studies can serve as the basis for an advanced control and scaled-up design that will ensure an economically feasible H 2 production.…”
Section: Introductionmentioning
confidence: 99%